STUDI KARAKTERISTIK PEMBENTUKAN UAP DALAM PEMBANGKIT UAP HELIKAL PADA REAKTOR MODULAR DAYA KECIL - Susyadi; Tjahjono, Hendro; Dibyo, Sukmanto; Pane, Jupiter Sitorus (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Small modular reactor (SMR) is very suitable to be deployed in Indonesia especially for locations having low electrical grid capacity, so further investigation on the characteritic of this reactor is needed. In general SMR has a compact and integrated-to-vessel steam generator design. This design implies different approach in producing steam as compared to conventional nuclear power plant having inverted u-tube steam generator. For that reason, this research is intended to investigate the steam characteristic and how it is generated in the helical SG which is widely used in SMR. The method used is through numerical calculation of the SG model using RELAP5 code. In the model, the feed-water which has low pressure and temperature is flown into helical tubes while high pressure and temperatur fluid, which represents reactor primary system coolant, stays in outer side of the tube. Calculation result shows that the steam produced by helical steam generator is superheated, i.e. about 25 K above saturation temperature. This provides comparative advantage to SMR on the design and operational aspects compared to conventional reactors because the superheated steam it produces can reduce turbine losses and at the same time increase thermodynamic efficiency.